Optimization and characterization studies of bio-oil production from Jathropa curcas L. husk by pyrolysis using response surface methodology / Salamiah Zakaria et al. - Zakaria, Salamiah; Ab Ghani, Zaidi; Md Isa, Mat Riduan; Abdul Rahman, Wahida; Uyup, Noor Hafizah; Md Yusof, Yuswanie (Universiti Teknologi MARA, Perlis, 2012)
Biomass is one of the energy resources that can be exploited to replace fossil fuel. Combustion, pyrolysis and gasification are the main process to convert biomass into valuable fuel materials. In this study, Jathropa curcas L. husk was pyrolyzed to produce bio-oil. The effect of several parameters on the pyrolysis efficiency were tested to identify the optimal condition for the bio-oil production. The tested parameters include temperature, heating rate and gas flow rate. The experiments were conducted using vertical fixed-bed reactor. The response surface methodology (RSM) with a central composite design (CCD), were used for optimization the process parameters. From the study, the optimal conditions were obtained at pyrolysis temperature of 400oC, heating rate of 60oC/min and gas flow rate of 100ml/min with the amount of bio-oil produced was 28.9%. Furthermore, the bio –oil produced under optimum condition was characterized by using elemental analyser, bomb calorimeter, Fourier Transform Infra-red (FT-IR) spectroscopy and gas chromatography-mass spectroscopy (GCMS).